Występowanie łosi Alces alces L. na terenie Lasów Rogowskich (środkowa Polska) - Gryz, Jakub; Krauze-Gryz, Dagny (Leśne Prace Badawcze, 2022)
Environmental changes affect edge populations first and the strongest. The aim of this study was to document the historical and current occurrence of the moose Alces alces L. along the western edge of its range in Poland and Europe. Our studies were conducted in central Poland, in the area of Experimental Forest Station of Warsaw University of Life Sciences (WULS) in the vicinity of Rogów village (225 km2 of field and forest mosaic, forest cover approx. 20%). We reviewed all available historical data as well as recorded direct observations. This included data collected through various methods such as drive counts, night spot-light and thermal vision counts along transect routes, snow tracking, camera-traps and pellet group counts. Occurrence of moose and changes in its abundance in the area of the Experimental Forest Station in Rogów reflected trends in the abundance of the species and in its range throughout the whole country. Currently, direct observations of moose or signs of its presence are recorded in the whole study area. However, in this very fragmented landscape, the species does not form a stable population but the observed individuals are most likely migrating from their main refugees. Signs of presence were recorded only once during drive counts and snow tracking in the central part of the study area (2011–2018) registered 0.03 moose tracks/km/24 h. Snow tracking conducted in January and February of 2021 was focused on moose specifically and revealed the presence of 10–11 individuals in the entire study area. Pellet group counts along transects (spring 2020 and 2021) resulted in a density index of 0.33 pellet groups/km/100 days of accumulation, while data from camera-traps (2011–2020) indicated an increase in the relative abundance index. In the biggest forest complex of the study area, this index increased three fold, whereas in smaller forest complexes only two fold. Assuming that 11 individuals were present, the population density was 0.49 ind./1000 ha in terms of total area and 2.6 ind./1000 ha in terms of forest area. In the following years, a further population increase can be expected reflecting growth in the core population.